TOURISM AS A KEY FACTOR OF ECONOMIC AND CULTURAL DEVELOPMENT (Ustozlar uchun, 2026)
Tourism is one of the fastest-growing industries in the modern world. It plays an important role in the economic, social, and cultural development of many countries. Tourism includes traveling for leisure, business, education, health, and cultural exchange. Today, millions of people travel from one country to another every year to explore new places, experience different traditions, and relax from daily life.The development of transportation, technology, and communication has made tourism more accessible and convenient. As a result, tourism has become a significant source of income and employment worldwide. This article discusses the importance of tourism, its types, advantages, disadvantages, and its impact on society and the environment.